M. Quraish Shihab dan Pengaruhnya terhadap Dinamika Studi Tafsir Al-Qur’an Indonesia Kontemporer - Rahmatullah, Rahmatullah; Hudriansyah, Hudriansyah; Mursalim, Mursalim (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
M. Quraish Shihab is often considered to be the scholar having the significant influence and role toward the study of the tafsir in contemporary Indonesia. However, the role and influence have not been well discussed yet. This writing found that M. Quraish Shihab indeed has a significant role and influence. Thematic tafsir which becomes the trend of the contemporary tafsir in Indonesia is formed under the influence and the role of M. Quraish Shihab. He was among the first to initiate and manage a thematic interpretation study project in the Indonesian academic world. In addition to being a supervisor for writing thematic interpretations carried out by his students, his activeness in producing works of thematic interpretations is also his wayof transmitting his exegesis ideas, and because of that he can influence the dynamics of contemporary Indonesian tafsir studies. Not only that, he also affects the dynamics of the object of study of the tafsir. This influence can be seen from the proliferation of studies that examine his commentary ideas and are inspired by his commentary ideas. In fact, his significant influence can also be seen from the emergence of variousappreciations and criticisms directed to him and his interpretative ideas.